Nap improved game-related technical performance and physiological response during small-sided basketball game in professional players - Maher Souabni; Omar Hammouda; Mehdi Souabni; Mohamed Romdhani; Wajdi Souissi; Achraf Ammar; Tarak Driss (Termedia Publishing House, 2022)
The effect of 40-min nap (NAP) opportunity on psycho-physiological outcomes and technical performance during small-sided basketball game (SSG) was examined in ten professional basketball players. Nocturnal sleep and naps were monitored by actigraphic recording and sleep diaries. Nocturnal total sleep time (TST), time in bed (TIB), sleep efficiency (SE), sleep onset latency (SOL) and wake after sleep onset (WASO) were analyzed. Subjective sleep quality was assessed with visual analogue scale (VAS). Profile of mood state (POMS) and simple reaction time (SRT) were measured before and after Nap and no-nap (CON) conditions. During both test sessions, participants played 10-min SSG. Technical and tactical performances were assessed using Team Sport Assessment Procedure. Volume of play (VP), attack with ball (AB), efficiency index (EI) and performance score (PS) were determined. Heart rate (HR) was measured during SSG, and rating of perceive excretion (RPE) after. Lower HR (p ≤ 0.03, d ≥ 0.78) and RPE (p = 0.007, d = 1.11) were obtained in NAP compared to CON. There was no significant difference in TIB, TST, SE, WASO and VAS between CON and NAP conditions. AB, EI and PS were higher in NAP compared to CON (0.0002 ≤ p ≤ 0.001, 1.3 ≤ d ≤ 1.8). A significant reduction was observed in POMS' fatigue (p = 0.005, d = -1.16, Δ = -53.6%), anxiety (p = 0.02, d = -0.9, Δ = -32.1%), anger (p = 0.01, d = -0.94, Δ = -30.3%), and an improvement in vigor (p = 0.01, d = 0.99, Δ = + 23.8%); which may reflect better readiness after nap and more concentration to start a game-situation. In summary, NAP reduced fatigue, anger, anxiety and enhanced vigor, allowing better technical and tactical performances during basketball SSG.